Evaluation of a laboratory-developed multiplex real-time PCR assay for diagnosis of syphilis, herpes and chancroid genital ulcers in four public health laboratories in the USA. (6th December 2021) - Koralur, Munegowda; Chen, Cheng Y; Pillay, Allan; White, Brunie; Pettus, Kevin; Chi, Kai-Hua; Stringer, Joey; Aroh, Chukwuemika; Dasu, Trivikram; Bhattacharyya, Sanjib; Perkins, Keith; Chen, Jenny; et al.
Abstract : Objective: To evaluate the field performance of a multiplex PCR (M-PCR) assay for detection of herpes simplex virus (HSV)-1 and HSV-2, Treponema pallidum ( T. pallidum ) and Haemophilus ducreyi ( H. ducreyi ) in genital ulcer disease (GUD) specimens. Methods: GUD M-PCR was performed on 186 remnant specimens, previously collected for HSV testing, by four public health laboratories (PHLs) and the Laboratory Reference and Research Branch (LRRB) at the Centers for Disease Control and Prevention. The results from the PHLs were compared with those of LRRB, which served as the reference testing method, and percentage agreement was calculated. Results: HSV was detected in 31 of 52 (59.6%), 20 of 40 (50%), 43 of 44 (97.7%) and 19 of 50 (38.0%) specimens from PHL1, PHL2, PHL3 and PHL4, respectively. There were seven discrepant results for HSV, and the overall percent agreement between the PHLs and the LRRB was 94%–100%, with a kappa value of 0.922, which demonstrates high agreement. T. pallidum was identified in 7 of 51 (13.7%) specimens from PHL1 with 94.1% agreement and in 2 of 40 (5.0%) specimens from PHL2 with 100% agreement. The LRRB identified three additional T. pallidum -positive specimens from PHL1. The kappa value (0.849) for T. pallidum testing suggests good agreement. Consistent with the LRRB results, no T. pallidum was detected in specimens from PHL3 and PHL4, and H. ducreyi was not detected at any of the study sites. Conclusions: The GUD M-PCR assay performed well in four independent PHLs and 12 suspected syphilis cases were identified in this study. The M-PCR assay could provide improved diagnostic options for GUD infections in state and local PHLs.